Clinical efficacy of Generic Meropenem (Penem®): Experience of Her Royal Highness Princess Maha Chakri Sirindhorn Medical Center, Faculty of Medicine, Srinakaharinwirot University (ผลการตอบสนองในทางคลินิกต่อยา Generic Meropenem(Penem): ประสบการณ์ของศูนย์) - Buppanharun, Wanchai; Tantisiriw, Woraphot (Journal of Medicine and Health Sciences, 2010)
Objective: To review the clinical efficacy of generic meropenem (Penem®) use in 17 patients. Method: A retrospective review of patients receiving Penem® for the treatment of Her Royal Highness Princess Sirindhorn Medical center Faculty of Medicine, Srinakaharinwirot University, Nakornnayok was carried out from December 2007 to May 2008. Results: From nineteen patients (11 males and 8 females) had received Penem® during the study period but 2 patients were excluded due to inadequate duration of treatment and non-susceptible causative pathogen. The infections included urinary tract infection (6 patients), respiratory tract infection (6 patients), intra-abdominal infections (2 patients) and bone-plate infection (1patient). Nine patients had infection caused by single organism, 6 patients had that caused by multiple organisms, and 2 patients had negative culture results. Seven patients had evidence of bacteremia, and 6 patients had evidence of clinical sepsis. Sixteen patients from 17 patients, who were infected with susceptible bacteria to Penem®, were improved with treatment. Conclusion: In our institute, Penem® can be prescribed to treat infections caused by susceptible strains.